2021
DOI: 10.3389/fpsyg.2021.664612
|View full text |Cite
|
Sign up to set email alerts
|

Cyberbullying Involvement, Resilient Coping, and Loneliness of Adolescents During Covid-19 in Rural China

Abstract: Cyberbullying involvement can lead to internal health issues, especially mental health problems. Different coping strategies may reduce or enhance the strengths between cyberbullying experience and mental health problems. In this study, we examined the correlations between cyberbullying involvement and loneliness among a group of children and adolescents during the Covid-19 pandemic in China, focusing on investigating the protecting effect of the resilient coping strategy. The results demonstrated that 86.68% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0
6

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(57 citation statements)
references
References 45 publications
1
23
0
6
Order By: Relevance
“…Our findings regarding the relationship between TB at work and depression [ 51 ], insomnia [ 3 , 90 ], and social isolation [ 91 , 92 ] are consistent with those from precedent research. It has been reported that CB victimization among adolescents is associated with loneliness [ 93 , 94 ] and sleep problems [ 95 ]. Our study expands the existing literature showing the negative effects of CB victimization on sleep and loneliness among employees.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings regarding the relationship between TB at work and depression [ 51 ], insomnia [ 3 , 90 ], and social isolation [ 91 , 92 ] are consistent with those from precedent research. It has been reported that CB victimization among adolescents is associated with loneliness [ 93 , 94 ] and sleep problems [ 95 ]. Our study expands the existing literature showing the negative effects of CB victimization on sleep and loneliness among employees.…”
Section: Discussionmentioning
confidence: 99%
“…During this pandemic, high school teenagers face the challenge of feeling lonely (Scott et al, 2021 ). Compared to children at the elementary and junior high school levels, high school students are reported to have higher levels of loneliness (Han et al, 2021 ). Loneliness is the leading cause of emotional reactions, namely, feeling sad in adolescents (Esposito et al, 2021 ).…”
Section: Resultsmentioning
confidence: 99%
“…It is therefore plausible that loneliness does not activate aggressive behavior online. In research, loneliness has been found more often in cybervictims, not cyberbullies, and as a consequence but not as a precursor of cyberbullying involvement (e.g., Olenik-Shemesh et al, 2012;Han et al, 2021). In a short-term longitudinal study by Schultze-Krumbholz et al (2012) the authors were able to show, though, that in boys cyberbullying reduced feelings of loneliness at the second measurement occasion.…”
Section: Discussionmentioning
confidence: 97%